Postoperative opioid-free analgesia in dogs undergoing tibial plateau leveling osteotomy: a feasibility study - Didier, Caroline; Faucher, Sarah; Sarra Ferrer, Marti; Lapouge, Mathilde; Junot, Stéphane; Jourdan, Géraldine (Frontiers in Veterinary Science, 2024)
Objec)ves: This study was designed to prospec;vely evaluate the feasibility of an opioid-free anesthesia protocol and describe the quality of recovery and management of postopera;ve analgesia in dogs aYer a ;bial plate levelling osteotomy (TPLO). Methods: Twenty dogs presented for TPLO were included. AYer premedica;on with intravenous (IV) medetomidine (0.005-0.007 mg/kg) and midazolam (0.2 mg/kg), anesthesia was induced with ketamine (2 mg/kg) and propofol and maintained with isoflurane and ketamine CRI (0.6 mg/kg/h). Scia;c and femoral nerve blocks were performed with bupivacaine 0.5% (0.087 +/-0.01 and 0.09 +/-0.02 mL/kg respec;vely). Meloxicam (0.2 mg/kg IV) was administered intraopera;vely, aYer osteotomy. Fentanyl (0.002 mg/kg IV) was administered intraopera;vely, as rescue analgesia in case of sustained increase in cardiorespiratory variables. Two pain scores (French 4A-VET and Glasgow short form) were performed at conscious sternal recumbency and 2, 4, 6, 8, 12 and 20 hours aYer extuba;on and compared to baseline using a Friedman test followed by a Nemenyi post-hoc test. Time to first food intake and urina;on were reported. Results: Intraopera;ve opioid-free anesthesia was feasible in 11 dogs, whereas 9 dogs received fentanyl once during arthrotomy. No opioid postopera;ve rescue analgesia was required. Food intake occurred within 6 hours and all dogs were discharged at 24 hours without any complica;on. Conclusion: Total opioid-free postopera;ve analgesia was achieved in all dogs, with adequate recoveries. If opioid-free anesthesia was feasible in 55% of the popula;on, a single dose of fentanyl was necessary in 45% of the dogs during arthrotomy.